Lessons learned from health and fitness prescription: a Malaysian experience (Faculty of Medicine Universitas Indonesia, 2007)
Proportion of chronic diseases sufferers are increased by age. The usual control measures are therapeutic prescription and clinical counseling. However, its low compliance rate has interfered this effort. Therefore, community intervention can be a suitable prescriptive option to provide a long lasting effect. For that, a package of community intervention has been established in one sub-urban area in Malaysia to observe its acceptability, thus it can be acted as a social instrumentation to bring both biological and social benefits to this group of community. This study used quasi-experimental design on a cohort of elderly citizen aged 45 and above. Respondents are exposed to a mixed and planned prescribed fitness activity using participatory approach. Process involved in program implementation is closely observed both quantitatively and qualitatively. Community participation occurred in a positive and fast mode, with 78% being the elderly people aged above 45 years old. Initial observation revealed that about 47.6% suffering hypertension, while 38.4% hypercholesterolemia, 16.8% obese and 7.1% diabetes mellitus. Physically active members were moderate - about 31.0%. In term of process, participatory approach seems to be very effective to mobilize community towards health and fitness. A planned community fitness program is a form of social instrumentation to bring biological and social benefits to chronic diseases sufferers. It has also useful to promote favorable lifestyle and quality of life of this group of people. (Med J Indones 2007; 16:39-46) Keywords: community intervention, community participation, fitness program, disease burden